EFFECTIVENESS OF FERMENTED Ul-va lactuca ON FEED ON GROWTH RATE OF CARP (Cyprinus carpio) - Nurbety Tarigan; Yatris Rambu Tega (Jurusan Perikanan dan Kelautan, 2022)
This research was conducted to determine the effectiveness of fermented Ulva lactuca in feed on the growth rate of tilapia and to determine the best dose of the effectiveness of fermented Ulva lactuca on the growth rate of tilapia. This study used a completely randomized design with four treatments and three replications of 0%, 10%, 20% and 30% on feed. The carp used with fish length ranging from 7-9 cm and an average body weight of 3-4 g were reared for 42 days. The results showed that the addition of fermented ulva lactuca had a significant effect on the specific growth rate of tilapia, survival rate, protein efficiency ratio (PER), protein utilization efficiency (EPP). The addition of 30 % fermented Ulva lactuca in the feed was the best dose for the growth rate of tilapia. The specific growth rate was 19.42%, the efficiency of protein utilization was 68.76%, and the protein efficiency ratio was 19.41% while the survival rate was 55.56%. The addition of Ulva lactuca in feed can increase the growth rate of tilapia.